Pengaruh Kompetensi dan Komunikasi Organisasi terhadap Motivasi Kerja Serta Dampaknya pada Kinerja Tenaga Penyuluh di Dinas Pertanian dan Ketahanan Pangan (DPKP) Kota Jambi - Maimun Maimun; Saiyid Syech; M. Zahari MS (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purpose of this study was to obtain an overview of competence, organizational communication, work motivation and employee performance at the Department of Agriculture and Food Security (DPKP) Jambi City; and to determine the influence of competence and organizational communication directly and indirectly on work motivation and employee performance; as well as to determine the effect of motivation on performance. To answer the research objectives, the authors need theoretical studies related to research variables, namely competency theory, organizational communication, motivation and performance. In addition, the authors also look for relevant previous research in the form of previous articles/journals and theses to support this research. The population in this study were extension workers from the Department of Agriculture and Food Security (DPKP) Jambi City with a total of 56 extension workers. The sampling technique in this study used Saturated Sampling, so that the number of samples in this study amounted to 56 extension workers. The results of the path analysis test carried out, the results of the study show that organizational competence and communication have an influence on employee motivation and performance, both directly and indirectly. Where based on the results of the t test (partial) and the F test (Simultaneous) show that organizational competence and communication have a significant and positive influence on motivation and performance, as well as motivation also has a significant and positive influence on performance. This explains that if competence and organizational communication can be carried out properly, it will have a positive influence in increasing work motivation which has implications for improving performance in the Jambi City DPKP. This study reveals that the competence, communication, motivation and performance of employees at the Jambi City DPKP are in fairly good condition; competence and organizational communication have a positive and significant impact on work motivation both directly and indirectly; competence and organizational communication have a positive and significant impact on employee performance both directly and indirectly; work motivation affects employee performance; and competence and organizational communication together through motivation can have a direct and indirect effect on employee performance at the Jambi City DPKP.